Consumers' attitudes towards locally manufactured high involvement products: a systematic review - Chinedu, Anyanwu Hilary; Haron, Sharifah Azizah; Hashim, Ahmad Hariza; Jo, Ann Ho (Canadian Center of Science and Education, 2020)
The increased level of market globalization has necessitated inculcation of positive attitudes towards locally manufactured high involvement products in consumers. While several governments are concerned about this, scholars have also given attention to this development and as a result, a need to ascertain what actually instigates consumers’ attitudes towards locally manufactured high involvement products such as: automobiles, houses, and mobile services through systematic review of extant literatures. A systematic literature review that involved comprehensive search of four databases utilized eight eligible studies to conclude that the influence of collectivism and consumer ethnocentrism (CE) on attitude towards locally manufactured high involvement products is a psychological process. The review also revealed that collectivism and CE catalyze consumers’ attitudes towards locally manufactured high involvement products through emotional and rational temperaments. Implications of the findings are discussed with suggestion for further studies.